PENGARUH LINGKUNGAN KERJA, BEBAN KERJA DAN KOMPENSASI TERHADAP LOYALITAS KARYAWAN DI PT MEGA BAJA PEMALANG - Sabilul Kirom; Rauly Sijabat; Sutrisno Sutrisno (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
This research aims to determine the influence of the work environment, workload and compensation on employee loyalty at PT Mega Baja Pemalang. Researchers used primary data obtained through distributing questionnaire forms via Google Form to employees at PT Mega Baja Pemalang. The population in this study were employees of PT Mgea Baja Pemalang. The technique used in sampling is non-probability sampling using saturated samples (census). The analytical tool used in this research uses SPSS. The results of this research are that the work environment has no effect on employee loyalty, workload has no effect on employee loyalty, and compensation has a significant effect on employee loyalty.